2014
DOI: 10.1590/1809-4503201400030018
|View full text |Cite
|
Sign up to set email alerts
|

Coorte de Carlos Barbosa

Abstract: O objetivo geral da coorte é avaliar a saúde bucal, a saúde geral, o estado nutricional, a qualidade de vida e os sintomas depressivos em idosos vivendo independentemente, na cidade de Carlos Barbosa, Rio Grande do Sul, Brasil. Carlos Barbosa é um município localizado a 104 km ao norte de Porto Alegre, capital do Rio Grande do Sul. Em 2004, ano em que a linha de base foi realizada, as estimativas revelam que a cidade tinha 22.215 habitantes, dos quais 2.167 tinham 60 anos ou mais.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…At the end, 872 subjects accepted to participate in the study (response rate of 88.7%). The methodology of the cohort study has been described in detail previously (baseline, sample size calculation, follow‐up and measures used) and is available in the literature …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end, 872 subjects accepted to participate in the study (response rate of 88.7%). The methodology of the cohort study has been described in detail previously (baseline, sample size calculation, follow‐up and measures used) and is available in the literature …”
Section: Methodsmentioning
confidence: 99%
“…The methodology of the cohort study has been described in detail previously (baseline, sample size calculation, follow-up and measures used) and is available in the literature. 19 Data collection included standardised interviews for the identification of the sociodemographic, behavioural and general health variables. The sociodemographic and behavioural data were as follows: age (in years), sex (male, female), education (years of study), marital status (married, single), individual monthly income (in Brazilian Reais), smoking behaviour (smoking at least 100 cigarettes in life yes/no), consumption of alcoholic beverages (yes/no) and frequency of visits to the dentist (regularly/occasionally/never).…”
Section: Materials S and Me Thodsmentioning
confidence: 99%
“…The city is also served by an extensive network of private dental care providers. Prior to the baseline study in 2004, the Brazilian census of 2000 revealed that the city had 20 519 inhabitants of whom 2167 were aged 60 years or more 15 . Estimates of the Brazilian Institute of Geography and Statistics revealed a population of 30 630 inhabitants in 2021.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to the baseline study in 2004, the Brazilian census of 2000 revealed that the city had 20 519 inhabitants of whom 2167 were aged 60 years or more. 15 Estimates of the Brazilian Institute of…”
Section: Me Thodsmentioning
confidence: 99%